Skin cancer risk among testicular germ‐cell cancer survivors: a systematic review and meta‐analysis. (9th February 2022) - Reiter, O.; Voss, V.B.; Fluss, R.; Boyce, L.M.; DeFazio, J.L.; Halpern, A.C.; Marghoob, A.A.
Abstract: Testicular germ‐cell tumours (TGCT) are the most common cancer among young adult men. Previous studies suggested TGCT survivors have an increased risk for skin cancer. The goal of this study was to systematically review the literature and evidence regarding skin cancer risk among TGCT survivors compared with the general population. PubMed, EMBASE, Web of Science, Cochrane Databases and reference lists were included in the search. A systematic review of all comparative studies with more than 10 TGCT survivors reporting on skin cancer incidence was performed. A meta‐analysis of the Standardized Incidence Rate (SIR) was calculated by pooling study‐specific log‐transformed estimates using the random‐effects model. Risk of bias was assessed using the Newcastle–Ottawa Quality Assessment Scale. Nineteen studies that reported on 147 935 TGCT survivors were included. Pooled SIR for skin cancer and for melanoma incidence among TGCT survivors were 1.93 (95% CI 1.62–2.29, P < 0.0001) and 1.81 (95% CI 1.57–2.08, P < 0.0001), respectively. In conclusion, compared to the general population, TGCT survivors have an increased risk for developing skin cancer and melanoma. Additional long‐term studies that include TGCT survivors, additional risk factors and all subtypes of skin cancer are required.